Effect of submillimeter size holes on the fatigue limit of a high strength tool steel. (12th November 2013) - Shyam, A.; Blau, P.; Jordan, T.; Yang, N.
ABSTRACT The very high cycle fatigue and small fatigue crack growth behaviour of a generic tool steel material for diesel fuel injector application are described. The small crack growth tests for the tool steel material with and without the hardening heat treatment revealed the mechanisms of crack propagation and threshold behaviour. Based on the small fatigue crack propagation threshold value, an elastic plastic fracture mechanics methodology for the prediction of the endurance limit of specimens with submillimeter holes is proposed. The advantages of the new methodology are discussed in relation to existing methodologies for endurance limit prediction of specimens with small holes.